Hybrid media events: the Charlie Hebdo attacks and the global circulation of terrorist violence - Sumiala, Johanna (Emerald Publishing Limited, 2018)
What are hybrid media events? Who creates them and what kind of purpose do they serve in contemporary societies? This book addresses these questions by re-thinking media events in the contemporary digital media environment saturated by intensified circulation of radical violence. The empirical analyses draw on the investigation of theCharlie Hebdo attacks in Paris, in 2015 and the global responses those attacks stirred in the media audience. This book provides a new way of thinking about the idea of the hybrid in global media events. The authors give special emphasis to the hybrid dynamics between the different actors, platforms and messages in such events, explaining how global news media, terrorists and political elites interact with ordinary media users in social media. It demonstrates how tweets such as "Je suis Charlie" circulate from one digital media platform to another and what kind of belongings are created in those circulations during the times of distraction. In addition, the book examines how emotions, speed of communication and fight for attention become hybridized in the digital media. All these aspects, the authors argue, shape the ways in which we make sense of global media events in the present digital age. The authors invite readers to critically reflect the technological, economical, political and socio-cultural challenges connected with today's global media events and the ethical encounters they may entail